PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI - Rhemananda, Hosea; Widaryanti, Widaryanti; Mohklas, Mohklas (STIE PENA, 2022)
This study aims to analyze the effect of Profitability, Managerial Ownership and Firm Size on Accounting Conservatism. With a sample of 40 Property and Real Estate companies listed on the Indonesia Stock Exchange in 2016-2019 selected using the purposive sampling method. The data obtained in this study used the documentation method. With multiple regression analysis method. The results of this study are profitability has a significant positive effect on accounting conservatism, managerial ownership has a positive and insignificant effect on accounting conservatism, firm size has a significant positive effect on accounting conservatism.Keywords: profitability, managerial ownership, firm size and accounting conservatism